Performance Analysis of Over Current Relay on 20 kV Distribution Network Feeders Using MATLAB - Arlina Hasibuan; Muhammad Daud; Raihan Putri (Journal of Power, Energy, and Control, 2025)
Short circuit disturbances in electrical distribution systems can cause severe damage to equipment and compromise system stability if not properly addressed. To mitigate these impacts and maintain system reliability, protection devices such as overcurrent relays (OCR) are widely used to detect and automatically isolate overcurrent conditions. This study aims to analyze the magnitude of short circuit current and evaluate the performance of OCR in responding to faults in a 20 kV medium-voltage distribution network. The analysis was conducted using MATLAB Simulink, modeling the distribution system with parameters adjusted to actual system conditions. The simulation was carried out under two scenarios: normal operating conditions to ensure the OCR remains inactive when the current is within safe limits, and fault conditions to evaluate the accuracy and speed of the OCR response to overcurrent events. Simulation results show that the magnitude of the short circuit current decreases with the distance from the source, with values of 5,565.92 A at 5% of the feeder length, 1,367.25 A at 25%, 698.52 A at 50%, 468.87 A at 75%, and 352.83 A at 100%. Under normal conditions, the current waveform remains stable throughout the 0.2-second simulation period. In contrast, under fault conditions, a current surge exceeding the threshold occurs at 0.1 seconds, triggering the OCR. The relay responds promptly and accurately in accordance with the designed inverse-time characteristics, demonstrating its effectiveness and reliability in detecting and clearing short circuit faults in 20 kV distribution networks.